The Art of Scientific Immobilisation of Animals - Nair, N. R. (Indian Forester, 1977)
This paper outlines the subject of chemical immobilisation of animals, briefly narrating different aspects such as pharmacology and mechanism of action of paralytic and anesthetic drugs darting equipment and complications arising out of im nobilisation procedures and also gives recommended dosages of some important drugs for the common Indian animals.